FAKTOR KLIEN YANG MEMENGARUHI PERGANTIAN KANTOR AKUNTAN PUBLIK DI BURSA EFEK INDONESIA - Suarjana, I Wayan; Sari Widhiyani, Ni Luh (E-Jurnal Akuntansi, 2015)
Auditor independence is the key to the auditing profession. In Indonesia, one of the ways to maintain the independence of the auditors is set in PMK number:17/PMK.01/2008 about "Public Accountant Services" with the rotation of auditors. Public and stakeholders will certainly wonder about the factors that cause the change of auditors outside the regulatory. This study examines the factors that affect company to make the change auditor among others, the audit opinion, the auditor's reputation, growth, firm size, and changes in profitability. Manufacturing companies listed in Indonesia Stock Exchange 2009-2012 period was the study population, the number of companies with a total sample of 62 observations as much as 248 companies. Sampling technique using purposive sampling method. Logistic regression analysis is a data analysis technique used. Testing of the hypothesis showed that the audit opinion variable positive and significant effect on the change of auditor. Variable growth negatively affect the change of auditor. Auditor reputation, size and profitability of the change has no effect on the change of auditor.
Keywords: change of auditor, audit opinion, auditor' s reputation, firm size, growth, profitability changes